RUANG BERUBAH BERSAMA-SAMA: ANTROPOLOGI DALAM TRANSFORMASI SOSIAL BUDAYA PAPUA - I Ngurah Suryawan (Studi Budaya Nusantara, 2018)
AbstrakThe biggest challenge of anthropology, especially in frontier areas (front lines) like in Papua, is to place it in the context of the vortex of the meaning of socio-cultural transformation experienced by humans themselves. Anthropology, thus becoming a